Intellectual property rights and ex-post transaction costs: the case of open and closed source software - Sebastian von Engelhardt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The economic characteristics of software and transaction costs explain, why closed source and open source software co-exist. It is about the efficient use of a non- and anti-scarce resource. But because of ex-post transaction costs that lead to information asymmetries, some property rights regarding the resource source code are not exclusively separable. Thus, the first best allocation of property rights, that would yield an optimal usage of a source code, is not realizable. Or, that is to say, a first best realization of contracts is not feasible. Hence, open and closed source software are two second best arrangements, both with specific assets and drawbacks. The principle of closed source benefits from direct (monetary) incentives and control, but has limits in its scope (size) because of transaction costs. Open source, on the one hand, benefits from its openness that creates spillovers and enables to incorporate human capital that is not acquirable for closed source firms. On the other hand, there are costs of openness, such as coordination costs (consensus finding, etc.) the danger of free riding or under provision, or forking.
Keywords: D23; L17; L22; O34; 330; Open source; intellectual property rights; transaction costs; information goods; modeling property rights; Software; Digitale Güter; Transaktionskosten; Immaterialgüterrechte; Software-Recht; Open Source; Theorie